KEARIFAN LOKAL MASYARAKAT DALAM MENGENDALIKAN API PADA AKTIVITAS LADANG BERPINDAH DI DESA PALA PULAU KECAMATAN PUTUSSIBAU UTARA KABUPATEN KAPUAS HULU - Afendy, Albertus; Lumangkun, Agustine; Manurung, Togar Fernando (Universitas Tanjungpura, 2017)
Local wisdom are any form of knowledge, belief, understanding or insight and habits or ethics that guide human behavior in life in an ecological community. This research was conducted in the village of Pala Island District of Putussibau North Kapuas Hulu Regency. The study aims to find out the form of local wisdom in the way of choosing land, clearing land and controlling the fire in the activity of the shifting cultivation. Factors measured in this study were: experience, age, education and length of stay in the village of Pala Pulau District of Putussibau North Kapuas Hulu, the sample was taken by purposive sampling technique. Primary data collection through direct interviews of 87 respondents through questionnaires. Data were analyzed using Chi Square analysis. Local knowledge and local ecological communities are still practiced by the community, in shifting cultivation activities such as land selection, land clearing and fire control in the form of techniques, rituals and certain rules in practice, this lesson is passed down from generation to generation to them. Villagers of Pala Pulau are still dependent on their life by shifting cultivation for their daily needs by utilizing the fertility of the land they are working on. Keywords: fire control, land, local knowledge, Local wisdom, shifting cultivation.